Benefits of Implementing a Complete Systematic Land Registration Program For Community-Owned Land - Zetria Erma (Fox Justi : Jurnal Ilmu Hukum, 2025)
The purpose of this study is to determine and analyze the benefits of implementing the Complete Systematic Land Registration (PTSL) program on community-owned land. This type of research is normative with a statutory approach. The data used is secondary data consisting of primary and secondary legal materials. The research specification used is descriptive analytical. The benefits of implementing the Complete Systematic Land Registration (PTSL) program on community-owned land are part of a government program that aims to accelerate the implementation of land registration activities to provide protection and legal certainty for community-owned land in the form of property rights certificates as a manifestation of the implementation of citizens' rights as stipulated in Article 28D paragraph (1) of the 1945 Constitution so as to create a single land map and land register in Indonesia. For this reason, it is recommended that both the government (BPN), local government and the community support this activity so that it can run smoothly by communicating and socializing between institutions and the community.